2016
DOI: 10.3389/fpubh.2016.00158
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Problems among Adolescent Students: An Exploratory Study in the Central Region of Nepal

Abstract: BackgroundRecently, schools have drawn attention as dominant factors for psychosocial development of students. Nepal, however, has limited studies on this issue. This study sought to assess the prevalence of psychosocial dysfunction and its association with family-related factors among adolescent Nepali students.MethodsTaking 787 adolescent students from 13 schools of Hetauda municipality, we accomplished a cross-sectional study. A set of structured questionnaire and Y-PSC was adopted to collect data, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
3
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(94 citation statements)
references
References 20 publications
(26 reference statements)
6
61
3
5
Order By: Relevance
“…Kumar KS et al (2017) 17 conducted his study among 800 higher secondary school students at Imphal using DASS tool found that 81.6% of respondents had at least one of the studied disorders (depression, anxiety and stress) and 34.7% had all these three negative states. Many studies conducted by different authors found prevalence of psychiatric morbidity to be lower than our study like Faizi N et al (2017) 18 at Aligarh conducted study among 13-15 years' age group school going adolescents, employing Strength and Difficulties Questionnaire (SDQ), reported prevalence to be 9.75%; Bista B et al (2016) 19 at Nepal conducted study among 787 adolescent students using a set of structured questionnaire and Y-PSC found prevalence to be 17.03%; Murthy NMR et al (2016) 20 conducted study at Mysore among 683 adolescent 21 at Faridkot conducted study among 500 children (6th to 12th standard), using tool Childhood Psychopathology Measurement Schedule (C.P.M.S), found prevalence to be 16.8%. This difference in prevalence rates is probably because of different settings, methodology and instruments used for data collection.…”
Section: Discussioncontrasting
confidence: 50%
“…Kumar KS et al (2017) 17 conducted his study among 800 higher secondary school students at Imphal using DASS tool found that 81.6% of respondents had at least one of the studied disorders (depression, anxiety and stress) and 34.7% had all these three negative states. Many studies conducted by different authors found prevalence of psychiatric morbidity to be lower than our study like Faizi N et al (2017) 18 at Aligarh conducted study among 13-15 years' age group school going adolescents, employing Strength and Difficulties Questionnaire (SDQ), reported prevalence to be 9.75%; Bista B et al (2016) 19 at Nepal conducted study among 787 adolescent students using a set of structured questionnaire and Y-PSC found prevalence to be 17.03%; Murthy NMR et al (2016) 20 conducted study at Mysore among 683 adolescent 21 at Faridkot conducted study among 500 children (6th to 12th standard), using tool Childhood Psychopathology Measurement Schedule (C.P.M.S), found prevalence to be 16.8%. This difference in prevalence rates is probably because of different settings, methodology and instruments used for data collection.…”
Section: Discussioncontrasting
confidence: 50%
“…For children and adolescents ages 6 through 16, a cutoff score of 28 or higher indicates psychological impairment. This scale showed high internal reliability (Cronbach's alpha-0.89 and 0.75) when used with Nepalese adolescents studying in various school and non-school settings (Banstola, 2015;Bista, et. al., 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, future studies are needed for a better understanding of the predictors of health risks and protective behaviors with both positive and negative health outcomes for adolescents in the Asian regions. Moreover, the differences in health status between different patterns of socio-demographic characteristics suggest future research and policy making in promoting psychosocial health among adolescents in Asia Pacific region [18]. A follow-up survey will be conducted between September 2020 and 2021 in the six regions of this study to yield new longitudinal evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The domains of quality of life, psychosocial, and mental health indicators were found to be intercorrelated in the literature [5][6][7][8][9][10][11][12][13], and these indicators at adolescence were associated with their well-being in adulthood [8,14,15]. In previous studies, the demographic characteristics such as family-related factors have been shown to be associated with quality of life and psychosocial health conditions among adolescents [16][17][18]. Lee, et al [19] found that adolescent lifestyle and social support were positively associated with quality of life and were different between Asian-Pacific countries.…”
Section: Introductionmentioning
confidence: 93%